A school for young ladies and a school for poor nursery schoolchildren. School architecture as a note on religious school diversity in provinces at the beginning of the 20th century - García-Lozano, Rafael Ángel (Historia y Memoria de la Educación, 2022)
In this paper we examine the educational work carried out in the city of Zamora from the beginning of the 20th century by the Company of the Daughters of Charity of St. Vincent de Paul in two schools run by the Order. They were opened precisely 40 years after the religious society’s arrival in the capital in 1860, in response to as request by the Provincial Charity Board to run the Nuestra Señora del Tránsito hospice. Four decades later, their initial welfare work took on an explicitly educational character with the management of two schools. Managed by the same religious institution, the school of the Patronato de San Vicente de Paúl started up in 1904, continuing the work of a school located in a city slum and poorly supported by the City Council with municipal funds after the elderly teacher who attended it ceased her work. Only a year earlier, in 1903, the Company also opened the Colegio Medalla Milagrosa, moved by the impulse of the provincial deputies, who wanted their daughters to receive an education at a level comparable to that given by the nuns to orphan girls in their orphanage. In this research, we focus on the analysis of their respective school architecture as an example of the diversity of the educational attention of the Company in Zamora.